Shiga Toxin–producing Escherichia coli Serotype O78:H(–) in Family, Finland, 2009 - Lienemann, Taru (Centers for Disease Control and Prevention, 2012)
Shiga toxin–producing Escherichia coli (STEC) is a pathogen that causes gastroenteritis and bloody diarrhea but can lead to severe disease, such as hemolytic uremic syndrome (HUS). STEC serotype O78:H(–) is rare among humans, and infections are often asymptomatic. We detected a sorbitol-fermenting STEC O78:H(–)stx(1c):hlyA in blood and fecal samples of a 2-week-old boy who had bacteremia and HUS and in fecal samples of his asymptomatic family members. The phenotypic and genotypic characteristics and the virulence properties of this invasive STEC were investigated. Our findings demonstrate that contrary to earlier suggestions, STEC under certain conditions can invade the human bloodstream. Moreover, this study highlights the need to implement appropriate diagnostic methods for identifying the whole spectrum of STEC strains associated with HUS.